2011
DOI: 10.1051/0004-6361/201016341
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the local interstellar magnetic field from non-thermal emission of SN1006

Abstract: Context. The synchrotron radio morphology of bilateral supernova remnants depends on the mechanisms of particle acceleration and on the viewing geometry. However, unlike X-ray and γ-ray morphologies, the radio emission does not depend on the cut-off region of the parent electron population, making it a simpler and more straightforward tool to investigate the physics of cosmic ray production in supernova remnants (SNRs). Aims. We will use the radio morphology to derive tight constraints on the direction of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 33 publications
8
44
0
3
Order By: Relevance
“…Orlando et al 2007;Fulbright & Reynolds 1990), or more specifically the case of SN 1006 ((e.g. Schneiter et al 2015;Bocchino et al 2011;Schneiter et al 2010).…”
Section: Polar-caps Vs Barrel-like Modelsmentioning
confidence: 99%
“…Orlando et al 2007;Fulbright & Reynolds 1990), or more specifically the case of SN 1006 ((e.g. Schneiter et al 2015;Bocchino et al 2011;Schneiter et al 2010).…”
Section: Polar-caps Vs Barrel-like Modelsmentioning
confidence: 99%
“…Because of the low surrounding density, the ionisation age of SN 1006 is one of the lowest measured in the Galactic supernova remnants. We used C-statistic to fit the data, which for a progressively higher number of counts asymptotically approaches the χ 2 value (Cash 1979). The best-fit model to the EPIC spectrum of the knot is a single non-equilibrium ionisation (NEI) model and a basic absorption model.…”
Section: Overall Spectramentioning
confidence: 99%
“…The remnant has a particular morphology, in the sense that X-ray synchrotron radiation seems to be emitted only in the northeastern and southwestern part of the remnant, with very little synchrotron emission along the line of sight toward the centre. The most viable explanation is that these synchrotron limbs are polar caps of the remnant, and the axis of the ambient magnetic field lies SW-NE (Rothenflug et al 2004;Völk et al 2003;Berezhko et al 2009;Bocchino et al 2011). Such a magnetic field parallel to the shock A&A 552, A9 (2013) This study is part of a large observing project on SN 1006 (PI: Decourchelle), which consists of seven XMM-Newton pointings that, coupled with archival data, bring the total observing time to ≈900 ks.…”
Section: Introductionmentioning
confidence: 99%
“…This is also in favor of the polar cap model. Finally, Bocchino et al (2011) compared an observed radio morphology at 1 GHz with synthesized radio maps based on 3D magnetohydrodynamic (MHD) simulations, finding that a model assuming quasi-parallel injection efficiency better represents the data than the quasi-perpendicular model. Direct estimates of the magnetic-field orientation were performed through radio polarization measurements for the bright lobes (Kundu 1970).…”
Section: Geometry Of Synchrotron Emissionmentioning
confidence: 99%